Hypolipidemic and cardioprotective effects of Taraxacum officinal aqueous extract in obese rats - Ikram, Toumi (Array, 2021)
Obesity is a chronic disease responsible for comorbidity and excess mortality, and is considered an independent risk factor for cardiovascular pathology development. Most cardiovascular disease can be prevented by tackling behavioural risk factors, such as a sedentary lifestyle, unhealthy diet, and obesity. Taraxacum officinal is a perennial plant belonging to the Asteraceae family, commonly used for these medicinal characteristics. It has diuretic, anti-tumour, antioxidant, anti-inflammatory, hepatoprotective and immunostimulant properties. The aim of this study was to evaluate the lipid-lowering and cardioprotective effect of Taraxacum officinal aqueous extract in Wistar rats on hyperfatty diets. A total of 24 rats weighing 200 ± 6.8 g were divided into three lots: healthy control (HC) receiving a standard diet, obese control (OC) receiving a cafeteria diet without treatment and the third load (TL) receiving a cafeteria diet and treated for 20 days with 200 mg/kg Taraxacum officinal aqueous extract. The results showed that the cafeteria diet induced obesity in rats compared to the control group, characterized by hyperglycaemia (148.75 mg/ dL), hypertriglyceridemia (59 mg/dL) and hypercholesterolemia (160.67 mg/dL) with an increase in total lipids (0.39 g/g of tissue) associated with a state of oxidative stress in the cardiac tissue. Oral administration of the aqueous extract of Taraxacum officinal improved the lipid profile in serum and tissue. The findings showed a drop in blood sugar (1.02 mg/dL), total cholesterol (135 mg/ dL), LDL cholesterol, (67 mg/dL), triglycerides (36 mg/dL), total lipids (1.37g/g of tissue), and lipid peroxidation MDA (0.25 ± 0.02 μmoL/g protein), and an increase in the level of GSH (0.51 nM /mg protein) in treated rats compared to the controls. In conclusion, the results obtained showed the effectiveness of the aqueous extract of Taraxacum officinal against dyslipidemia, obesity, and hyperglycaemia.